SCIENCE AND RELIGION IN LATIN AMERICA: DEVELOPMENTS AND PROSPECTS. Issue 2 (June 2015) - Silva, Ignacio
Abstract The state of the debate surrounding issues on science and religion in Latin America is mostly unknown, both to regional and extra‐regional scholars. This article presents and reviews in some detail the developments since 2000, when the first symposium on science and religion was held in Mexico, up to the present. I briefly introduce some features of Latin American academia and higher education institutions, as well as some trends in the public reception of these debates and atheist engagement with it in Mexico and Argentina. The primary conclusion of this article is that, even though the discussion is new to Latin American academic circles, it is gaining traction and will certainly grow in the coming years.